Selection of processing parameters for the laser directed energy deposition process applied to additive manufacturing: a methodological proposal - Thiesen Junior, Anselmo (2021)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Campus Joinville, Programa de Pós-Graduação em Engenharia e Ciências Mecânicas, Joinville, 2021.